Envolvimento dos receptores NMDA e imidazolínicos nos efeitos das poliaminas sobre a preferência condicionada por lugar induzida por morfina - Girardi, Bruna Amanda (2020)
Morphine use disorder is a chronic disease involving biological, cognitive and behavioral changes that develop after repeated and compulsive substance use. Even after long periods of abstinence relapses occur to users, especially when faced with situations that resemble the use thereof. The dopaminergic system is critically involved in the process of development and maintenance of drug-related memories, and the glutamatergic system acts modifying its activity. Arcaine [ARC, antagonist of polyamine binding site at glutamatergic N-metyl-D-aspartate receptor (NMDAr)], modulating the morphine reward system and positive allosteric modulators of NMDRr, such as spermidine, also modifies the conditioned morphine response. Thus, the aim of the present study was to investigate the involvement of glutamatergic and imidazolinic receptors in the effect of polyamines on the consolidation, expression, extinction and reinstatement of morphine-induced conditioned place preference (CPP, a behavioral test used to verify the rewarding effects of different substances). Adult male albino Swiss were preconditioned once a day for 15 minutes for two consecutive device in the CPP, in the next day, twice a day, were subjected to conditioning sessions with different drugs and protocols for four consecutive days. Twenty-four hours after the last conditioning session the animals were subjected to the test. After the post-conditioning test, the animals were subjected to daily extinction testing sessions that consisted of exposure to the apparatus with free access to both compartments for 15 min. The preference score was assessed as the difference between the amount of time spent in the drug-paired compartment in the Pre-CPP phase and the amount of time spent in the drug-paired compartment on the day of testing (Post-CPP) and on the days of extinction sessions. The results of this study showed that spermidine (10-30 mg/kg) facilitated the extinction of morphine-CPP, while ifenprodil (a NMDAr antagonist, 0.1 mg/kg, rate without effect per se) prevented the facilitatory effect of spermidine. Treatment during the extinction period with spermidine prevented the reinstatement of the extinct morphine-CPP, however, ifenprodil (1 mg/kg) did not alter. Arcaine (3 mg/kg), idazoxan (antagonist of imidazolinic and α2 -adrenergic receptors, 0.5-5 mg/kg) and yohimbine (antagonist α2 -adrenergic, 2.5-10 mg/kg) did not induce preference on its own, but yohimbine, prevented the morphine-induced CPP in a dose dependent manner. These results suggest that spermidine facilitate the extinction and prevents the reinstatement of morphine-CPP probably by binding to the GluN2B subunit of NMDAr and that the effect of arcaine on consolidation and expression of morphine-CPP occurs through the activation of imidazolinic receptors. Thus, the present study provides evidence of the therapeutic potential of polyamines in the persistent interruption of adaptive memories related to morphine dependence. In addition, this evidence added to the fact that polyamines are already being used in humans, through dietary supplementation, to treat cognitive deficits, make polyamines interesting prototypes in the development of drugs for treatment of psychoactive drug-related disorders.